Implementasi Pendidikan Karakter Religius Di Sekolah Dasar - Muhammad Dhori; Tiara Nurhayati (eL Bidayah: Journal of Islamic Elementary Education, 2022)
The background of this research is the increasing incidence of character devia-tions in the community which shows the weak behavior of students. This is due to the lack of maximum enforcement of religious character in schools. The purpose of the study was to describe the implementation, strategy, and sup-porting aspects as well as aspects of the implementation of religious character education in elementary schools. The writing method uses descriptive qualita-tive and literature review. The data to support the writing of this journal pa-per comes from the literature related to the problem being studied. Various kinds of reference books, namely books, papers, proceedings, scientific journals, and scientific articles come from the internet. Writing maximizes mutual con-tinuity with each other and in accordance with the subject matter. The data obtained are filtered and sorted by subject matter. Then, do writing papers based on data that has been designed which are mutually sustainable in a co-herent manner. The data study method is descriptive and argumentative. The results showed that the implementation of religious character implemen-tation can be seen from 1) The dimensions of the religious character developed. 2) The strategy is implemented through layers of artifacts and layers of values and beliefs. 3) Supporting factors and inhibiting factors. The method in shap-ing the religious character of the students is packaged in the subject matter as well as in the school environment. Thus, the teacher has the most important role in shaping religious character. Regarding how to use it, there are model guides, story methods, and traditional ways of doing things. [Latar belakang dari penelitian ini adalah makin maraknya kejadian penyim-pangan karakter dalam lingkungan masyarakat yang menunjukkan lemahnya perilaku peserta didik. Hal itu disebabkan kurang maksimalnya penegakan karakter religius di sekolah. Tujuan penelitian adalah mendeskripsikan pelaksanaan, strategi, serta aspek penunjang serta aspek implementasi pendidikan karakter religius di Sekolah Dasar. Metode penu-lisan menggunakan kualitatif deskriptif dan kajian kepustakaan. Data-data untuk menunjang penulisan makalah jurnal ini bersumber kepustakaan ber-sangkutan masalahan yang ditelaah. Berbagai macam acuan pustaka yaitu buku, makalah, prosiding, jurnal ilmiah, dan artikel ilmiah berasal dari inter-net. Penulisan memaksimalkan saling berkesinambungan satu sama lain dan sesuai dengan pokok pembahasan. Data diperoleh disaring serta diurutkan dengan pokok pembahasan. Lalu, melakukan penulisan karya tulis ber-dasarkan data yang sudah dirancang yang saling berkesinambungan secara runtut. Metode kajian data bersifat deskriptif argumentatif. Hasil penelitian menunjukkan bahwa pelaksanaan implementasi karakter religius dapat dilihat dari 1) Dimensi karakter religius yang dikembangkan. 2) Strategi yang dilaksanakan melalui lapisan artifak dan lapisan nilai dan keyakinan. 3) Faktor pendukungnya dan faktor penghambatnya. Metode da-lam membentuk karakter religius peserta didik tersebut dikemas dalam ma-teri pelajaran serta di lingkungan sekolah. Sehingga, guru mempunyai peran paling penting untuk membentuk karakter religius. Mengenai cara dipakai ialah panduan teladan, cara kisah, serta cara hal kebiasaan]